Impact of parenting style disparities on mental health of medical college students: an analysis of mediating effects of positive psychological qualities - Yang, Li; Song, Aili; Wu, Yanan; Wang, Xusheng; Liu, Yuting (Frontiers in Public Health, 2025)
BackgroundResearch has shown that parenting style disparities have a significant impact on the mental health of college students. However, the underlying reasons behind this phenomenon have not been sufficiently explored. This study systematically examines the impact of parenting style disparities on the mental health of medical college students from the perspective of positive psychology and analyzes the mediating effects of positive psychological qualities.MethodThis study administered questionnaires to 3,387 medical students in Wuhu, China, all of whom came from two-parent families. Specifically, the Short-Egna Minnen av. Barndoms Uppfostran for Children (s-EMBU-C) questionnaire was used to assess parenting style disparities, whereas the SCL-90 scale was utilized to evaluate mental health problems. Additionally, the Chinese College Student Positive Psychological Quality Scale was employed to assess positive psychological qualities. The hypothesis is proposed that positive psychological qualities mediate the relationship between parenting style disparities and mental health problems, and the bootstrap method was employed to examine the mediating effect. Additionally, a multivariate linear regression model was utilized to identify the factors associated with mental health problems.ResultsThe study revealed a significant positive correlation between parenting style disparities and mental health problems (r = 0.152, p < 0.01); conversely, parenting style disparities were significantly negatively correlated with positive psychological qualities (r = −0.070, p < 0.01). Additionally, positive psychological qualities were significantly negatively correlated with mental health problems (r = −0.201, p < 0.01). Furthermore, positive psychological qualities played a partial mediating role between parenting style disparities and mental health problems, accounting for 12.398% of the total effect.ConclusionParenting style disparities significantly negatively predict positive psychological qualities in medical college students, whereas positive psychological qualities significantly negatively predict mental health problems. Positive psychological qualities play a partial mediating role between parenting style disparities and mental health problems among medical college students. The main findings emphasize the importance of consistent parenting styles and the cultivation of positive psychological qualities for the mental health of medical college students.